Slum upgrading policies in Rio de Janeiro: institutional and normative aspects - Ximenes, Luciana Alencar (2023)
The state’s institutional capacity and regulatory framework are important fields of disputes over space production and recognition of social rights. Such disputes gain special relevance in the city of Rio de Janeiro, marked by intense social inequalities. In this context, slum upgrading policies consolidated between the 1990s and 2010s represent an important recognition of slums as popular housing spaces. The article analyzes the slum upgrading policies implemented in Rio de Janeiro during this period, focusing on institutional models and regulatory frameworks. It places the policies within the local political contexts, having the right to adequate housing as a guide. The study reveals the continuity and relative centrality of these policies in the analyzed period; however, it highlights important contradictions and limitations.